Manajemen Keuangan Syariah: Perannya terhadap Produkivitas Usaha Mikro, Kecil dan Menengah (UMKM) - Aswin Aswin; Yolanda Destiana; Muhammad Nurdin (Universitas Islam Negeri Sumatera Utara, 2025)
This research aims to analyze the important role of Sharia financial management in increasing the productivity of micro, small, and medium enterprises (MSMEs). The application of Sharia principles in financial management for micro, small, and medium enterprises (MSMEs), which offers aspects of justice, equality, responsibility, and non-exploitation, can be an effective solution for financial management based on Islamic values. This research is a qualitative study using a literature study approach by analyzing various accountable sources, including books, scientific journals, and data presented by Sharia financial institutions. Content analysis is conducted in three stages: data reduction, data presentation, and drawing conclusions from the collected data. The research results show that the application of Sharia principles in the financial management process plays an important role in increasing the productivity of micro, small, and medium enterprises (MSMEs). This is due to increased consumer trust, the minimization of potential risks, and ease of access to financial services at Sharia financial institutions